2009
DOI: 10.1103/physrevb.80.075423
|View full text |Cite
|
Sign up to set email alerts
|

Splitting in the Fermi surface ofZrTe3: A surface charge density wave system

Abstract: The electronic band structure and Fermi surface of ZrTe3 was precisely determined by linearly polarized angle-resolved photoelectron spectroscopy. Several bands and a large part of the Fermi surface are found to be split by 100-200 meV into two parallel dispersions. Band structure calculations reveal that the splitting is due to a change of crystal structure near the surface. The agreement between calculation and experiment is enhanced by including the spin-orbit potential in the calculations, but the spin-orb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…38 The CDW-induced enhancement in D(E F ) near the vHs may lead again to superconductivity or CDW stability. Particularly, in the narrow band that constructs the quasi-1D + 3D FSs together with the wide band, 11,16,17 electrons can form local pairs that interact attractively with each other over short distances. In other words, the formation of local pairs of electrons with Bose characteristics will be expected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The CDW-induced enhancement in D(E F ) near the vHs may lead again to superconductivity or CDW stability. Particularly, in the narrow band that constructs the quasi-1D + 3D FSs together with the wide band, 11,16,17 electrons can form local pairs that interact attractively with each other over short distances. In other words, the formation of local pairs of electrons with Bose characteristics will be expected.…”
Section: Resultsmentioning
confidence: 99%
“…We notice characteristic changes in the electronic band structure across the CDW transition, in which D(E F ) very close to the vHs is greatly enhanced in addition to significant electronic structural changes in the quasi-1D FS. 16,17 It is known that the presence of a vHs at E F can induce Fermi surface instabilities and lead to the superconducting state 36,37 or the CDW state. 38 The CDW-induced enhancement in D(E F ) near the vHs may lead again to superconductivity or CDW stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic and optical properties of various types of bulk TMTs such as ZrSe 3 , HfSe 3 , TiS 3 , ZrS 3 , ZrTe 3 have been investigated experimentally. [13][14][15][16] Previous studies have shown that, bulk TiS 3 is an n-type semiconductor with an energy band gap of 1 eV and it was shown that, it has a room temperature electronic mobility of about 30 cm 2 V −1 s −1 . 17 A nonlinear current-voltage characteristics of bulk TiS 3 has been observed below 60 K. 18 Compared to TMDs, TMTs have drawn little attention until recently, which changed when the single layer TiS 3 was isolated.…”
Section: -12mentioning
confidence: 99%
“…An initial interpretation of this was a structural relaxation of the van der Waals gaps below the surface [1,4] and it was shown theoretically that an increased van der Waals gaps could indeed give rise to two-dimensional electronic states that are similar to those observed by ARPES [11,12]. In related layered systems with van der Waals gaps, such a surface relaxation can in fact reproduce observed splittings of ARPES band dispersions [13]. Intercalating of atoms into Bi 2 Se 3 to increase the van der Waals gap spacing on purpose, however, did not lead to changes in the electronic structure [14], and an alternative interpretation of the phenomenon is the formation of twodimensional electron gases near the surface caused by an adsorbate-induced band bending [9,10,15,16].…”
mentioning
confidence: 92%